Maintenance model based on lean and TPM to increase machine availability in an SME in the plastic sector - Abad Mendoza, Jorge Sebastian (2025)
The plastics industry has grown in recent years due to growing demand in sectors such as construction and transportation, contributing 4% of the industrial GDP and employing more than 200,000 workers in the country. However, it has been identified that companies in the sector operate with low availability (70.83%) due to various production problems, including hours lost due to lack of machine maintenance. On the other hand, because of these problems, demand exceeds supply due to the low availability of the companies in the plastics sector. The literature review suggests that Lean Manufacturing (SMED, Standardization of Work, 5S) and the TPM (Total Productive Maintenance) technique are necessary tools to solve these problems. Finally, the implementation of these tools will allow solving the mentioned problems by increasing availability by 90%.